Penerapan Algoritma Frequent Pattern Growth pada Aplikasi Pembelian Obat Berbasis Web pada Apotik Sumber Sehat : Studi Kasus: Apotik Sumber Sehat - Elfrida Susanti Tanggu; Gergorius Kopong Pati; Alexander Adis (Neptunus: Jurnal Ilmu Komputer Dan Teknologi Informasi, 2025)
The implementation of the Frequent Pattern Growth (FPG) algorithm in a web-based drug purchasing application at Sumber Sehat Pharmacy aims to improve efficiency and accuracy in analyzing customer drug purchasing patterns. The FPG algorithm is a method used to identify frequent purchase patterns or frequent itemsets in purchase transactions, which can then be used to make relevant drug recommendations for customers. This study uses a case study at Sumber Sehat Pharmacy to explore drug purchasing patterns and provide a data-driven solution that can help pharmacies improve service and adjust drug stocks according to customer needs. The results show that the application of the FPG algorithm can identify significant purchasing patterns and assist pharmacies in determining more appropriate promotional strategies and inventory management. By using a web-based application that implements this algorithm, Sumber Sehat Pharmacy can provide drug recommendations that are more in line with customer preferences, thereby increasing customer satisfaction and pharmacy operational efficiency.